Early SOX9 Activation Primes Hippo– YAP / TAZ Rewiring During Glioblastoma Stemness Acquisition - Maimaitili Mijiti; Yandong Li; Aierpati Maimaiti; Gaocai Zhang; Minghao Lian; Chunyu Song; Yongtao Zhang; Jufan Wang; Yunbo Wang; Xiaoqin Chen; Xiangrui Kong; Xiahela Xiaokaiti; et al. (Journal of Cellular and Molecular Medicine, 2026)
ABSTRACT Glioblastoma progression is driven by stemness acquisition and cellular plasticity, yet the temporal and spatial organization of these processes remains incompletely defined. In this study, single‐cell RNA sequencing, pseudotime reconstruction, spatial transcriptomics, and in vitro and in vivo functional assays were integrated to delineate the role of SOX9 during glioblastoma stemness acquisition. SOX9 expression peaked during the early astrocyte‐to‐malignant transition and declined after malignant states became stabilized. Along pseudotime, SOX9 was inversely associated with the upstream Hippo kinase module and showed phase‐dependent coupling with YAP/TAZ‐associated transcriptional programmes. Spatial analyses further revealed marked regional heterogeneity, with the strongest SOX9‐malignant coupling observed in the perivascular niche. Functionally, SOX9 gain and loss produced reciprocal changes in glioblastoma cell proliferation, migration, invasion, apoptosis, and xenograft growth, while pharmacological modulation of Hippo signalling partially rescued the effects induced by SOX9 loss. Consistent pathway‐level changes were also observed in YAP/TAZ expression and p‐YAP/YAP and p‐MOB1/MOB1 ratios, and xenograft histology showed SOX9‐associated morphological and CD68‐positive cell changes. These findings identify SOX9 as a temporally restricted regulator of glioblastoma stemness acquisition and support an early priming‐late decoupling model of Hippo‐YAP/TAZ rewiring, providing a rationale for stage‐specific and niche‐aware therapeutic targeting in glioblastoma.